Strategi Guru PAI dalam Memotivasi Belajar Siswa di SMPN 8 Muaro Jambi - Saputra, Indrian; Budiman, Arif; Rinaldi, Rinaldi; Al Firdaus, Al Firdaus (Yayasan Abdurrauf Cendekia Nusantara, 2024)
Teachers have an important role in motivating students because teacher success in learning can be seen from the motivation and enthusiasm for learning of their students. Likewise, at SMPN 8 Muaro Jambi, a teacher needs to increase students' learning motivation because researchers still find several problems such as students who are not focused when studying, a learning atmosphere that is not yet conducive, lack of student attention, and low interest in learning. Given the above problems, this research aims to understand how PAI teachers increase the learning motivation of class VIII C students at SMPN 8 Muaro Jambi. This research uses a qualitative approach with data collection techniques in the form of observation, interviews and documentation. The research results show that PAI teachers apply various teaching methods, giving assignments, giving grades, and giving praise to increase students' learning motivation. However, there are several obstacles faced, such as students' lack of interest in PAI lessons, peer influence, lack of parental attention and supervision, and limited PAI lesson hours. Keywords: teacher strategy, Islamic religious education, student learning motivation. Abstrak: Guru memiliki peran penting dalam memotivasi siswa sebab keberhasilan guru dalam pembelajaran dilihat dari motivas dan semangat belajar siswanya. Sama halnya di SMPN 8 Muaro jambi perlu seorang guru meningkatkan motivasi belajar siswa sebab peneliti masih menemukan beberapa masalah seperti siswa yang tidak fokus saat belajar, suasana pembelajaran yang belum kondusif, kurangnya perhatian siswa, dan rendahnya minat belajar. Dengan adanya masalah di atas penelitian ini bertujuan untuk memahami bagaimana guru PAI meningkatkan motivasi belajar siswa kelas VIII C di SMPN 8 Muaro Jambi. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa guru PAI menerapkan berbagai metode pengajaran, memberikan tugas, memberikan nilai, dan memberikan pujian untuk meningkatkan motivasi belajar siswa. Namun, terdapat beberapa kendala yang dihadapi, seperti kurangnya minat siswa terhadap pelajaran PAI, pengaruh teman sebaya, kurangnya perhatian dan pengawasan orang tua, serta jam pelajaran PAI yang terbatas.